Canine Cutaneous Extragenital Venereal Granuloma (CCEVG): Clinical and Pathological Features, Diagnostic Approach, and Treatment Strategies - Parikh, Naiya P.; Panchal, Mahesh T. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Transmissible venereal tumor (TVT) is a contagious neoplasm affecting canines that is primarily transmitted through the transfer of malignant cells during coitus. TVT is a rare example of a naturally occurring allograft cancer, and studies have suggested that it may have originated from an individual dog or wolf that lived approximately 11,000 years ago (Murchison et al., 2014). The tumor is characterized by its predominantly extra-genital manifestations, which may develop from the implantation of neoplastic cells on exposed mucosae, as well as its unique genetic features. For instance, TVT has an unusual karyotype that is believed to have arisen from a rearrangement of the normal canine chromosomes, resulting in the maintenance of a stable tumor genome across the population of TVT cells (Bongiovanni et al., 2016). Young dogs, stray dogs and sexually active dogs are most regularly affected by this tumour (Nak et al., 2005). It is classified into two groups, genital TVT and extragenital TVT, depending upon the sites of the tumour mass is present (Das and Das, 2000). The most common site of TVT is the caudal penile region in male dogs and the posterior vagina region in female dogs, with the tumor frequently surrounding the urethral orifice and protruding from the vulva if located within the vagina. In rare cases, TVT may develop at extra-genital sites. Macroscopically, TVT lesions are often friable, with a low cohesion between the neoplastic cells, resulting in their propensity to hemorrhage. This tendency towards bleeding, in conjunction with the formation of nodular, granulomatous, or necrotic masses, typically forms the first clinical sign observed in affected animals. Diagnosis of TVT often involves a combination of clinical presentation, cytology, histopathology, and immunohistochemistry to differentiate it from other neoplasms. While TVT can cause significant morbidity, several chemotherapeutic agents have shown to be highly effective in treating it. Hence, this report describes canine cutaneous extragenital venereal granuloma (CCEVG) in three dogs: its clinical and pathological features, diagnostic approach, and treatment strategies.